On deferred statistical convergence of order ? of sequences of fuzzy numbers - Et, Mikail; Erol, Yuksel (Ios Press, 2018)
The main purpose of this paper is to introduce and examine the concepts of deferred statistical convergence of order beta and strong r-deferred Cesaro summability of order beta for sequences of fuzzy numbers and give some relations between deferred statistical convergence sequences of order beta and strongly r-deferred Cesaro summable sequences of order beta, where beta is an element of (0, 1] and p is an element of R+.
Keywords: Fuzzy number; statistical convergence; deferred cesaro mean